A FAMILIES IN CRISIS - Kahveci, Müedin (International Scientific Journal Vision, 2017)
There are numerous factors that can influence one family and its functioning. This paper refers only to certain factors which can influence family functioning, its development and thus indirectly affect mental health of family members. Developmental and no developmental, willing and unwilling family crises are seemingly inevitable part of every family system. Experts in the area of mental health, family psychotherapists or experts in the area of family functioning should aim their activities towards facilitating of families to meet a variety of crises as effectively as possible. It is, thus, important to build up the family resources, or abilities to identify the options provided by those resources, for overcoming of crises. During the process of family functionality support, awareness of family members should be raised concerning the importance and options that relevant institutions have to offer to a family in crisis through different educative forms, seminars, debates, etc. as stressed by Ackerman (Ackerman, 1966) tendency towards psychical health is not a luxury but a necessity of one family, and both the individual and the society as a whole.